Employee engagement during COVID-19 in Malaysia - Mustaffa, Amira; Lajuma, Surianti; Wider, Walton (Frontiers in Sociology, 2022)
This study's objective was to examine the effect of communication, training and development, and transformational leadership on employee engagement during COVID-19 in Malaysia. Four hundred individuals were recruited and data was analysed using partial least square structural equation modelling (PLS-SEM). Communication, training and development, and transformational leadership were found to positively affect employee engagement. In the midst of the COVID-19 outbreak, this study investigates these factors as components of the reciprocal process between employee and employer and their effects on employee engagement, thereby making original theoretical contributions. This study also provides vital insights for businesses to consider when designing effective employee engagement plans for their future well-being in the workplace.